rBaltMIP, a recombinant alpha-type myotoxin inhibitor from Bothrops alternatus (Rhinocerophis alternatus) snake, as a potential candidate to complement the antivenom therapy - Santos-Filho, Norival A. [UNESP]; Sousa, Tiago S.; Boldrini-Franca, Johara; Santos-Silva, Ludier K.; Menaldo, Danilo L.; Henrique-Silva, Flavio; Cintra, Adelia C. O.; Laure, Helen J.; Mamede, Carla C. N.; Oliveira, Fabio; Riul, Thalita B.; Dias-Baruffi, Marcelo; et al. (Elsevier B.V., 2016)
Phospholipase A(2) inhibitors (PLIs) are important targets in the search and development of new drugs. This study aimed at evaluating the potential of an alpha-type phospholipase A(2) inhibitor from Bothrops alternatus (Rhinocerophis alternatus) snake in its recombinant form (rBaltMIP) to complement the conventional antivenom therapy. Biochemical experiments showed that rBaltMIP presented pl 5.8 and molecular masses of similar to 21 kDa by SDS-PAGE and 19.57 kDa by MALDI/TOF MS. After tryptic peptides sequencing, the results were compared with other PLIs available in databases, showing 100% identity between rBaltMIP and its native inhibitor BaItMIP and from 92% to 96% identity with other inhibitors. Myotoxic activities of BthTX-1 and BthTX-II toxins were measured via plasma CI(levels, showing myotoxic effective concentrations (EC50) of 0.1256 p.g/ 1, and 0.6183 mu g/mu L, respectively. rBaltMIP neutralized the myotoxicity caused by these two toxins up to 65%, without promoting primary antibody response against itself. Nevertheless, this recombinant PLI was immunogenic when standard immunization protocol with Freud's adjuvant was used. In paw edema assays, EC50 of 0.02581 mu g/mu L and 0.02810 mu g/mu L, respectively, were observed with edema reductions of up to 40% by rBaltMIP, suggesting its use as an additional antivenom. In addition, myotoxicity neutralization experiments with the myotoxin BthTX-I showed that rBaltMIP was more effective in inhibiting muscle damage than the conventional anti venom. Thus, considering the severity of envenomations due to Bothrops alternatus (Rhinocerophis alternatus) and the low neutralization of their local effects (such as myotoxicity) by the current anti venoms, rBaltMIP is a promising molecule for the development of novel therapeutic strategies for clinical applications. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Bothrops alternatus; rBaltMIP; Phospholipase A(2) inhibitor; alpha PLI